Antimicrobial and Antibiofilm Properties of Latvian Honey against Causative Agents of Wound Infections - Ingus Skadiņš; Krišs Dāvids Labsvārds; Andra Grava; Jhaleh Amirian; Laura Elīna Tomsone; Jānis Ruško; Arturs Viksna; Dace Bandere; Agnese Brangule (MDPI AG, 2023)
Honey is widely used in traditional medicine and modern wound healing biomaterial research as a broad-spectrum antimicrobial, anti-inflammatory and antioxidant agent. The study's objectives were to evaluate the antibacterial activity and polyphenolic profiles of 40 monofloral honey samples collected from beekeepers in the territory of Latvia. The antimicrobial and antifungal activity of Latvian honey samples were compared with commercial Manuka honey and the honey analogue sugar solutions-carbohydrate mixture and tested against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, clinical isolates Extended-Spectrum Beta-Lactamases produced Escherichia coli, Methicillin-resistant Staphylococcus aureus and Candida albicans. Antimicrobial activity was evaluated with the well-diffusion method (80% honey solution w/v) and microdilution method. The honey samples with the highest antimicrobial potential were tested to prevent biofilm development and activity against a preformed biofilm. The principal component analysis of the antimicrobial properties of honey samples vs. polyphenolic profile was performed. Eleven honey samples exhibited antibacterial activity to all investigated bacteria. The antibacterial effect of the samples was most significant on the Gram-positive bacteria compared to the studied Gram-negative bacteria. Latvian honey presents promising potential for use in wound healing biomaterials, opening the possibility of achieving long-term antibacterial effects.